(untitled) (European Journal of Economics, Finance and Business Development, 2024)
The principles of successful operation of higher education institutions and the market of educational services are studied. Factors affecting the educational services market are presented. The main directions of effective planning of the educational process are analyzed. It is based on the principles of higher education services market formation.